2009
DOI: 10.1029/2009gl040218
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of global precipitation extremes

Abstract: [1] Data from the Global Precipitation Climatology Project (GPCP) covering the period 1979 -2007 are examined for changes of precipitation extremes as a function of global mean temperature by using a new method which focuses on interannual differences rather than time series. We find that the top 10% bin of precipitation intensity increases by about 95% for each degree Kelvin (K) increase in global mean temperature, while 30%-60% bins decrease by about 20% K À1 . The global average precipitation intensity incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
192
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(209 citation statements)
references
References 26 publications
12
192
0
2
Order By: Relevance
“…In addition, the precipitation records of 10 intensity bins on the global scale were studied using the GPCP pentad precipitation data from 1979 to 2007. Coupled analysis with global temperature was carried out following a relatively new technique introduced by Liu et al [20]. The following conclusions are drawn through the above analysis:…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the precipitation records of 10 intensity bins on the global scale were studied using the GPCP pentad precipitation data from 1979 to 2007. Coupled analysis with global temperature was carried out following a relatively new technique introduced by Liu et al [20]. The following conclusions are drawn through the above analysis:…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this way, quantitative contributions of global temperatures to precipitation can be extracted despite various factors that may affect precipitation characteristics. This method was first introduced by Liu et al [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tropical observations reveal a distinct link between rainfall extremes and temperature, with more/ less frequent heavy rain events during warm/cold periods [17]. Liu et al [18] found that the upper 10% of extreme precipitation intensified by about 95% for each degree Kelvin increase in global mean temperature. However, there are different regional patterns because of various regional climatic characters.…”
mentioning
confidence: 99%